Population structure and genetic diversity of traditional sweet cassava accessions in Mato Grosso, Paraná, Santa Catarina and São Paulo States, Brazil - Weslaine de Almeida Macedo; Pedro Soares Vidigal Filho; Maria Celeste Gonçalves-Vidigal; Stephanie Mariel Alves; Giselly Figueiredo Lacanallo; Mariana Vaz Bisneta; Filipe Schmidt Schuh (Acta Scientiarum. Agronomy, 2026)
With the increasing demand for more productive cultivars that are tolerant or resistant to diseases and pests, the exploration of genetic resources combined with molecular analyses has proven to be an essential research strategy. Through molecular analysis, it is possible to identify and select desirable traits with high precision, increasing the efficiency of breeding programs. This study aimed to analyze the population structure and genetic diversity of traditional sweet cassava accessions collected from rural and peri-urban areas of municipalities in the states of Mato Grosso, Paraná, Santa Catarina, and São Paulo States, Brazil, via microsatellite markers. A total of 227 traditional sweet cassava accessions were evaluated using 29 microsatellite markers. The analysis revealed polymorphisms across all loci, with an average of 3.21 alleles per locus and 12 rare alleles identified within the population, potentially linked to unique genetic traits. The mean polymorphism information content (PIC) value of 0.52 suggests that the markers were moderately to highly informative. The average observed heterozygosity (Ho) was 0.65, whereas the average genetic diversity was 0.60. The sweet cassava accessions were grouped into four subpopulations on the basis of population structure at K = 4. The PhiPT value was 0.13, indicating low to moderate genetic differentiation among the evaluated subpopulations and highlighting their distinct genetic characteristics. The most divergent combinations were observed between the accessions from Western Paraná and Northern Mato Grosso, as well as between accessions from Northern Mato Grosso and Central-Western Santa Catarina. These results are important for addressing aspects related to germplasm conservation and the demands of genetic improvement programs, which benefit from high genetic variability, for the development of new sweet cassava cultivars.